PERSEPSI SISWA TERHADAP PELAKSANAAN PEMBELAJARAN GEOGRAFI DI SMA NEGERI 5 BUKITTINGGI - novira azrun; Khairani Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This research have purpose to determine about how student’s perception of the implementation of learning geography in SMA Negeri 5 Bukittinggi, This research is a quantitative research with descriptive method. This research used questionnaire as instrument. Population of this research is students grade XII IPS with total 156 students, sample selection using the Random Sampling method with the provisions using the Krecjie’s table, with a total of 93 students. Result of this research show that implementation of learning geography in SMA Negeri 5 Bukittinggi in sufficient category with 48.4% wih detail at opening phase in deficient category with 61.3%, instructional phase in sufficient category with 46.2%, closing phase in deficient category with 53.8%.